Giant colonic diverticulum: Clinical presentation, diagnosis and treatment: Systematic review of 166 cases - Nigri, Giuseppe (World J Gastroenterol, 2015)
AIM: To investigate the clinical presentation, diagnosis, and treatment of giant colonic diverticulum (GCD, by means of a complete and updated literature review). GCD is a rare manifestation of diverticular disease of the colon. Less than 200 studies on GCD were published in the literature, predominantly case reports or small patient series. METHODS: A systematic review of the literature was performed using the Embase and PubMed databases to identify all the GCD studies. The following MESH search headings were used: “giant colonic diverticulum”; “giant sigmoid diverticulum”. The “related articles” function was used to broaden the search, and all of the abstracts, studies, and citations were reviewed by two authors. The following outcomes were of interest: the disease and patient characteristics, study design, indications for surgery, type of operation, and post-operative outcomes. Additionally, a subgroup analysis of cases treated in the last 5 years was performed to show the current trends in the treatment of GCD. A GCD case in an elderly patient treated in our department by a sigmoidectomy with primary anastomosis and a diverting ileostomy is presented as a typical example of the disease. RESULTS: In total, 166 GCD cases in 138 studies were identified in the literature. The most common clinical presentation was abdominal pain, which occurred in 69% of the cases. Among the physical signs, an abdominal mass was detected in 48% of the cases, whereas 20% of the patients presented with fever and 14% with abdominal tenderness. Diagnosis is based predominantly on abdominal computed tomography. The most frequent treatment was colic resection with en-bloc resection of the diverticulum, performed in 57.2% of cases, whereas Hartmann’s procedure was followed in 11.4% of the cases and a diverticulectomy in 10.2%. An analysis of sixteen cases reported in the last 5 years showed that the majority of patients were treated with sigmoidectomy and en-bloc resection of the diverticulum; the postoperative mortality was null, morbidity was very low (1 patient was hospitalized in the intensive care unit for postoperative hypotension), and the patients were discharged 4-14 d after surgery. CONCLUSION: Giant colonic diverticulum is a rare manifestation of diverticular diseases. Surgical treatment, consisting predominantly of colonic resection with en bloc resection of the diverticulum, is the preferred option for GCD and guarantees excellent results.